COMPETENŢA DE COMUNICARE ÎN ACTIVITATEA DIDACTICĂ - USM ADMIN (Moldova State University, 2011)
Communication Competence in Didactic Activity. We presented several issues of teacher-student communication. Educational communication has the advantage of provoking a complex dialogue. Through didactic communication, we understand a psychic and social process of influencing through particular language types, signs and symbols, the students' attitudes, behaviors, convictions, the motivational, affective, and volition components.